Quality of Primary Health Care During the COVID-19 Pandemic: Evaluation by Users Affected by the Disease - Nascimento, Murilo César do; Silva, Simone Albino da; Oliveira, Anne Andrade Matiazi de; Moura, Heriederson Sávio Dias; Araújo, Juliana Soares Tenório de; Delpino, Felipe Mendes; Soares, Debora de Almeida; Fronteira, Inês Santos Estevinho; Sawada, Namie Okino; Arcêncio, Ricardo Alexandre (O Mundo da Saúde, 2022)
The coronavirus disease pandemic greatly impacted society, creating unprecedented challenges for science, healthcare systems, and Primary Health Care, which were quickly charged with diversified responses to face this public health emergency. The objective of this study was to evaluate the quality of PHC from the perspective of people affected by COVID-19. This was a cross-sectional study with cases of COVID-19 in a Brazilian municipality. We used an electronic questionnaire with sociodemographic and clinical characteristics (of our own elaboration) and the PCATool-Brazil Instrument – for adult patients (reduced version), through the KoBoToolbox resource. After a pre-test and pilot study, data collection took place between January 11 and October 5, 2021. Descriptive statistics were used, calculating the General PHC Score – 0 to 10 (mean and standard deviations). 91 participants evaluated the PHC characteristics/ components. The overall PHC score (mean) was 4.4 (SD=1.9). This low overall PHC score obtained indicates weaknesses in the quality of this level of healthcare, in the first six months of the pandemic in 2020. Such a low PHC quality score is unprecedented. It appears that the negative result in the studied municipality reflects the impact of COVID-19 and the strategies adopted to face the pandemic triggered by SARS-CoV-2 in Brazil and in the world.